2004
DOI: 10.1038/sj.onc.1207651
|View full text |Cite
|
Sign up to set email alerts
|

Adult human mesenchymal stem cell as a target for neoplastic transformation

Abstract: The neoplastic process may involve a cancer stem cell. This concept has emerged largely from the careful analysis of tumour biopsy systems from haematological, breast and brain tumours. However, the experimental systems necessary to provide the cellular and molecular evidence to support this important concept have been lacking. We have used adult mesenchymal stem cells (hMSC) transduced with the telomerase hTERT gene to investigate the neoplastic potential of adult stem cells. The hTERT-transduced line, hMSC-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
228
1
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(247 citation statements)
references
References 27 publications
13
228
1
5
Order By: Relevance
“…The cells employed in these cultures were however not obtained from healthy individuals but isolated from subcutaneous fat during operation of complicated appendicitis and it is thus likely that they are not comparable to normal MSC Kassem et al, 2005). The second study broaches the issue of spontaneous transformation in the unphysiological case of immortalizing human MSC with hTERT, thereby gaining high levels of telomerase activity Serakinci et al, 2004). Such MSC showed various genetic and epigenetic changes in spite of maintaining a normal karyotype Serakinci et al, 2004).…”
Section: Msc and Transformation Riskmentioning
confidence: 99%
“…The cells employed in these cultures were however not obtained from healthy individuals but isolated from subcutaneous fat during operation of complicated appendicitis and it is thus likely that they are not comparable to normal MSC Kassem et al, 2005). The second study broaches the issue of spontaneous transformation in the unphysiological case of immortalizing human MSC with hTERT, thereby gaining high levels of telomerase activity Serakinci et al, 2004). Such MSC showed various genetic and epigenetic changes in spite of maintaining a normal karyotype Serakinci et al, 2004).…”
Section: Msc and Transformation Riskmentioning
confidence: 99%
“…In Rattus norvegicus, the gene was identified as a bone morphogenetic protein/retinoic acid-inducible transcript in the brain and is involved in perinatal development of sympathetic neurons (Kawano Toshiyuki and Ichiro, 2004). DBC1 expression is lost by promoter hypermethylation in bladder tumours, hepatocellular carcinomas and during transformation in hMSC transduced with the hTERT gene, indicating an important tumour suppressor role in addition to its role in the developing nervous system (Habuchi et al, 1998;Yu et al, 2003;Serakinci et al, 2004). Thus, DBC1 could have multiple functions in eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that hypermethylation of DBC1 is one of the earliest events in the development of transitional cell carcinoma (TCC) (Habuchi et al, 2001). Recently, loss of DBC1 expression by promoter hypermethylation was reported during transformation of adult mesenchymal stem cells (hMSC) transduced with the hTERT gene (Serakinci et al, 2004), where methylation correlated with the acquisition of the tumorigenic phenotype. Thus, DBC1 alteration might be one of the essential changes during neoplastic development in hMSC.…”
Section: Introductionmentioning
confidence: 99%
“…En utilisant des CSM immortalisées après transduction de hTERT (human telomerase reverse transcriptase), on a pu montrer que la transformation des CSM est un processus long et multi-étapes qui fait intervenir la délétion de p16 ink4a [22]. Depuis 2005, différents articles avaient rapporté que les CSM en culture (issues de moelle osseuse ou de tissu adipeux) présentaient des anomalies caryotypiques (anomalies de structure) et finissaient par se transformer et exprimer un potentiel oncogénique [23,24].…”
Section: La Stabilité Génétique Des Csmunclassified
“…La sénescence et la transformation sont des processus liés ; ainsi les cellules devenant sénescentes peuvent se transformer après une crise transitoire et l'abrogation des mécanismes de sénescence avec une réaug-mentation de la longueur des télomères ou la répression de l'activité de p16 ink4a et de p53 [22]. Par ailleurs, les cellules devenant sénescentes ont un phénotype sécrétoire spécifique avec production de différentes molécules comme l'IL6 (interleukine 6), des MMP (métalloprotéases), l'hepatocyte growth factor, le FGF2 et GROa (la chimiokine CXCL1).…”
Section: Le Contrôle Des Csm Cultivéesunclassified